KOMUNIKASI ANTAR PRIBADI DOSEN DAN MAHASISWA DALAM MEMOTIVASI BELAJAR MAHASISWA ILMU KOMUNIKASI UNIVERSITAS HANG TUAH PEKANBARU - Rudi Rahman (LPPM STISIP Persada Bunda, 2023)
Lecturers and students have a close relationship in building good learning motivation. Through learning when lectures take place is a major effort in developing the potential possessed by these students, motivation plays an important role in creating a quality learning process. This can be realized, of course, cannot be separated from the role of the lecturer who always socializes students in the educational aspect. Socialization is also carried out in the learning process including in increasing the learning motivation of these students. The stimulus and response that occurs between students and lecturers will affect the lecture objectives that have been prepared previously. This is because between motivation and results are always related to each other. This research is a qualitative descriptive study in which the results of this study explain that the communication that exists between lecturers and students in motivating learning for Communication Science students at Hang Tuah University Pekanbaru is carried out face-to-face or directly and also indirectly through WhatsApp media. Through personal communication between lecturers and students, lecturers try to provide motivation and direction for students to have high learning motivation. Messages delivered persuasively and messages conveyed by lecturers lead to the achievement of lecture objectives to be achieved by students